The horse who drank the sky : film experience beyond narrative and theory - Pomerance, Murray, 1946- (Rutgers University Press, 2008)
The author argues in this book that what is most important for cinema is that we are alive with it and that for all its dramatic, literary, political, sociological, and philosophical weight, film is ultimately an art that provokes, touches, and riddles the viewer through an image that transcends narrative and theory.